Rhizobium spp exopolysaccharides production and xanthan lyase use on its structural modification - de Sousa, Bruna Fernanda Silva [UNESP]; Castellane, Tereza Cristina Luque [UNESP]; Campanharo, João Carlos [UNESP]; de Macedo Lemos, Eliana Gertrudes [UNESP] (Elsevier, 2019)
Enzymes can be very useful on exopolysaccharides (EPS) research, can be used at elucidation and also to modify the polysaccharides' structure in order to alter their physical properties. Thus, the reduction of the molecular mass could increase applications of these biopolymers. Therefore, the EPS production of different rhizobia and the action of xanthan lyase on its structures were evaluated. The strains produced significant amounts of EPS, and it was noticed that are heteropolysaccharides, composed galactose and glucose. Both EPS and xanthan were modified on β-glycosidic bonds, the mannose was removed of xanthan had but the EPS was affected in the C[dbnd]O stretching vibration, where the glucuronic acid removed from of your structure. The ester/carboxylic acid portions affected functional groups of the acetate/succinate, methyl carbons of the O-acetyl and pyruvate methyl groups in addition to affect the carbons the main pyranoid. The Resistance to temperature increase of the EPS was observed, made possible by the activity of the lyase. EPS has the ability to form stable gels at higher temperatures and anionic feature can be used on solubilization and controlled release of substances. Modified EPS knowledge will presently facilitate future investigations relating the structure of the rhizobia polysaccharide against rheological properties.
Keywords: Infrared spectroscopy; Polysaccharide lyase; Rhizobia